Subcutaneous Fat Necrosis of the Newborn With Initial Hypocalcemia and Familial Recurrence: A Case Report. Issue 2 (March 2018) - Kellar, Amelia; Tangtatco, Jennifer Aileen; Weinstein, Miriam; Saunders, Natasha
Subcutaneous fat necrosis of the newborn (SFNN) is a rare disorder characterised by indurated plaques or nodules with or without erythema, typically distributed over the cheeks, extremities, posterior trunk, buttocks, and thighs, and appears during the first 2 weeks of life. It is commonly associated with perinatal asphyxia and, while usually self-limited, can lead to severe hypercalcemia. There is no known familial association. The present article describes a neonate with extensive disease, counterintuitive hypocalcemia, and a family history of SFNN and reviews the existing literature on SFNN.